Earmarked Green Tax Benefits and Flood Risk Experience Shaping Public Support and Compliance Intentions - Indriastuti, Eka; Markhumah, Umatun (Inovasi Analisis Data, 2025)
Purpose: This paper investigates the effects of flood mitigation benefit perceptions, governance aspects and disaster severity on perceptions towards and intentions to comply with green taxation. Method: A cross-sectional study with PLS-SEM approach was carried out on data collected digitally from flood-prone areas. Findings: The findings show that the perceived benefits of targeted flood mitigation programs, environmental effectiveness, fairness, and trust in the government significantly encourage support for green taxes and the intention to comply with them. Perceptions of transparency and accountability have a weaker direct effect. The impact of flooding does not directly influence support, but it has an important moderating effect. This means that it increases the effect of targeted benefits and perceptions of fairness on the intention to comply. Findings show that, in disaster-affected areas, residents assess green taxes not based on abstract environmental goals, but based on specific benefits that are in line with the principle of fairness. Novelty: This study proposes the flood impact severity as a contextual moderator in the association between cope-green tax design and disaster experience and rearticulates green taxation less in terms of control-of-emissions and more as adaptive climate-finance. Implications: The results of the study indicate that public acceptance of green taxes can be increased if the government allocates the revenue from these taxes to visible flood prevention efforts, ensures a fair distribution of the burden, and strengthens institutional credibility in areas vulnerable to climate risks.